Choline Alleviates Disorders of Lipid Metabolism in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus) Caused by High-Lipid Diet. (6th May 2022) - Li, Tao; Yan, Xiaobo; Dong, Xiaohui; Pan, Simiao; Tan, Beiping; Zhang, Shuang; Suo, Xiangxiang; Li, Zhihao; Huang, Weibin; Yang, Yuanzhi; Zhang, Haitao
Abstract : This study was conducted to evaluate the effect of dietary choline levels on growth performance, liver histology, lipid metabolism and related gene expression of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus ) fed high-lipid diets. The fish (initial body weight 6.86 ± 0.01   g ) were fed diets containing different choline levels (0, 5, 10, 15, and 20 g/kg, named D1, D2, D3, D4, and D5, respectively) for 8 weeks. The results shows that (a) dietary choline levels had no significant effect on the final body weight (FBW), weight gain rate (WGR), and specific growth rate (SGR) compared with the control group (P > 0.05 ); (b) with the increase in choline levels, triglyceride (TG), total cholesterol (TC), lipoprotein lipase (LDL), and high-density lipoprotein (HDL) of serum, all showed a tendency to increase and then decrease, and the maximum values were obtained in the D4 group (P < 0.05 ); (c) TG and TC in the liver showed a tendency to decrease first and then increase with the dietary choline levels and reached the minimum value in D3 and D4 groups, respectively (P < 0.05 ); (d) with increased choline levels, hepatic lipase (HL), lipoprotein lipase (LPL), adipose triglyceride lipase (ATGL), and fatty acid synthetase (FAS) in the liver all showed a tendency to increase and then decrease, and the maximum values were obtained in the D4 group, except ATGL that the maximum value was obtained in the D3 group (P < 0.05 ); (e) oil red staining showed that dietary choline significantly reduced hepatic lipid deposition; (f) choline supplementation significantly upregulated the expression of lipolytic genes lipoprotein lipase ( lpl ), hormone-sensitive lipase ( hsl ), and peroxisome proliferator-activated receptor α ( pparα ) and inhibited the expression of lipid synthesis genes fatty acid synthetase ( fas ), acetyl-CoA carboxylase α ( accα ), and peroxisome proliferator-activated receptor γ ( pparγ ). In summary, choline can promote lipid metabolism of hybrid grouper by regulating lipid metabolism-related enzyme activity and gene expression and mitigating the negative effects of high-lipid diets.